Chronic pain and group B vitamins - E. V. Zonova; L. I. Alekseeva; A. M. Lila (Современная ревматология, 2025)
Chronic pain (CP) impairs quality of life and increases the risk of non-communicable diseases and mortality. Pain is variable, and different mechanisms of its development determine the tactics of patient treatment. Researching pathogenesis of different types of pain can serve as a prerequisite for the development of more effective treatment approaches. The introduction of drug combinations into clinical practice enables a better response to treatment with lower doses, thereby reducing drug burden and potential toxicity.The review presents studies that address the question of how the efficacy of chronic pain therapy can be increased by including adjuvants in the treatment regimen, particularly a vitamin B complex.